2011 49th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2011
DOI: 10.1109/allerton.2011.6120374
|View full text |Cite
|
Sign up to set email alerts
|

Rate region of the vector Gaussian one-helper source-coding problem

Abstract: We determine the rate region of the vector Gaussian one-helper source-coding problem under a covariance matrix distortion constraint. The rate region is achieved by a simple scheme that separates the lossy vector quantization from the lossless spatial compression. The converse is established by extending and combining three analysis techniques that have been employed in the past to obtain partial results for the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This addresses the first issue. One can verify that if X is a vector and Y is a scalar, then the second and third issues do not arise, and hence distortion projection together with Oohama's converse arguments is sufficient to solve the problem [7]. Liu and Viswanath [4] showed that the channel enhancement technique of Weingarten et al [3] is sufficient to solve the helper problem in the vector case, thereby addressing the third issue.…”
Section: It Follows Thatmentioning
confidence: 95%
See 3 more Smart Citations
“…This addresses the first issue. One can verify that if X is a vector and Y is a scalar, then the second and third issues do not arise, and hence distortion projection together with Oohama's converse arguments is sufficient to solve the problem [7]. Liu and Viswanath [4] showed that the channel enhancement technique of Weingarten et al [3] is sufficient to solve the helper problem in the vector case, thereby addressing the third issue.…”
Section: It Follows Thatmentioning
confidence: 95%
“…Source enhancement and Oohama's converse technique are lifted directly from [1] and [6]. The distortion projection, on the other hand, requires an extension beyond what was needed in the scalar helper case [7]. This extension requires us to first establish several properties of the optimal Gaussian solution to the problem, to which we turn next.…”
Section: It Follows Thatmentioning
confidence: 97%
See 2 more Smart Citations
“…The Gaussian one-helper problem with the covariance matrix distortion constraint was studied in [13], [14]. Here in addition to a main encoder which observes the direct source and sends a message to the decoder with rate R 1 , there is a helper with noisy observations, which sends a message with rate R 2 to the decoder.…”
Section: Motivationmentioning
confidence: 99%